2009
DOI: 10.1159/000258692
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Immunoglobulin Reduces Infarct Volume but Not Edema Formation in Acute Stroke

Abstract: Objectives: Intravenous immunoglobulin (IVIG) is used for treatment of immunodeficiencies and autoimmune disorders. Recently, IVIG has also been shown to reduce infarct size in acute stroke. Since edema treatment can provide secondary neuroprotective effects, we conducted the present study to evaluate whether edema reduction is the underlying cause of the neuroprotective properties of IVIG in experimental stroke. Methods: Male Wistar rats received either IVIG or placebo and were subjected to temporary middle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
1
13
0
1
Order By: Relevance
“…A high concentration of IVIg has been reported to exert protective effects in neurons during ischemic conditions. 21, 23, 24 The present results demonstrate for the first time that IVIg modulates ischemic stroke-induced NLRP1 and NLRP3 inflammasome levels, with a corresponding downregulation of the pro-inflammatory cytokines IL-1 β and IL-18.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…A high concentration of IVIg has been reported to exert protective effects in neurons during ischemic conditions. 21, 23, 24 The present results demonstrate for the first time that IVIg modulates ischemic stroke-induced NLRP1 and NLRP3 inflammasome levels, with a corresponding downregulation of the pro-inflammatory cytokines IL-1 β and IL-18.…”
Section: Discussionsupporting
confidence: 54%
“…21 The pleiotropic effects of IVIg in inhibiting multiple components of inflammation in different cell types make it an attractive candidate for use in stroke therapy. 21, 22, 23, 24 Potential effects and underlying mechanisms of IVIg on inflammasome activation in ischemic stroke-induced neuronal cell death have not been reported. In the present study, we performed a comprehensive investigation of the dynamic expression patterns of the NLRP1 and NLRP3 inflammasome in primary cortical neurons subjected to simulated ischemia, in a mouse model of focal ischemic stroke, and in brain tissue samples from stroke patients.…”
mentioning
confidence: 99%
“…We [2,3] and others [10,11] have previously demonstrated that IVIg treatment reduces brain infarct volume and mortality in experimental rodent models of stroke. This study reveals a protective effect of IVIg against endothelial dysfunction following ischemic stroke, in association with reduced leukocyte infiltration in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…IVIG may serve as a potential therapy to compensate the deprivation of naturally occurring Aβ Abs in AD that would alleviate the Aβ-induced toxicity. Alternatively, IgG antibodies unrelated to specific Aβ Abs may have beneficial effects against Aβ toxicity as IgG has been shown to protect brain also against acute brain injuries [36,37]. However, the detailed mechanisms how IVIG treatment improves the AD pathology and cognitive defects are unclear.…”
Section: Introductionmentioning
confidence: 99%